Determinants of Low Birth Weight in Neonates Born in Three Hospitals in Brong Ahafo Region - Adam , Z. (University of Ghana, 2016)
Introduction: Low birth weight is the weight of the newborn measured immediately after birth and is less than 2500 grams. The global prevalence of LBW is 15.5 percent, which amounts to about 20 million LBW infants born each year. A high proportion (96.5%) of LBW babies are born in developing countries (Wardlaw, T., Blanc, A., Zupan, J., & Ahman, E. 2005). In Ghana, the recent incidence of LBW infants was estimated at 160 per 1000 births and has not witnessed any reduction in the last decade (Kayode et al., 2014). In the Brong Ahafo region the estimated prevalence of LBW is 91.9 per 1000 live births with a neonatal mortality rate at 6.6 per 1000 live births (DHIMS 2015). The objective of the study is to determine the factors that influence low birth weight (LBW) delivery in three hospitals in the Brong Ahafo Region. Method: Unmatched Case-control study design was used; A case was defined as a mother who delivers a baby with a birth weight below 2500grams in any of the study sites and a control defined as mothers with delivery of a baby with weight between 2500 grams and 3400 grams at the same site as a case within 24 hours of delivery of the case. A sample of 120 cases and 240 control mothers with singleton deliveries were recruited for the study. Case controls were collected in a ratio of 1:2 respectively. Three hospitals in Brong Ahafo Region, Ghana were used as the study sites. Results: The factors with their adjusted odds which influenced the delivery of a low birth weight baby included; first trimester hemoglobin <11g/dl(aOR 3.14; 95%CI 1.50-6.58), delivery at 32-36weeks gestation (aOR 13.70; 95%CI 4.64-40.45), delivery below 32weeks gestation (aOR 58.50; 95%CI 6.66-513.87), Secondary Education of mothers (aOR 4.19; 95%CI 1.45-12.07), living with extended family (aOR 2.43; 95%CI 1.15-5.10, living alone during pregnancy (aOR 3.95; 95%CI 1.33-11.74), and not taking iron supplements during pregnancy (aOR 3.19; 95%CI 1.07-9.54) were found to be the determinant factors of LBW . Conclusion: The study in these three facilities showed that the determinant factors for the delivery of a LBW were; delivery at preterm, Educational level of mothers being secondary, living alone during pregnancy, not taking iron supplementation and mothers with first trimester hemoglobin below 11g/dl.
Thesis(MPHIL)-University of Ghana, 2016
Keywords: Low Birth Weight; Neonates Born; Brong Ahafo Region